The Relationship Between Financial Literacy, Budgeting Behavior, and Household Economic Stability in Urban Communities - Eko Cahyo Mayndarto; Arisky Andrinaldo; Bobokulov Sanjar Baxronkulovich (Harmoni Economics: International Journal of Economics and Accounting, 2024)
This study explores the significant role of financial literacy in shaping household budgeting behaviors and its impact on economic stability, particularly in urban households. By analyzing data from 300 urban households, the study reveals that financially literate households manage their expenses more effectively, saving, on average, 20% more annually compared to their less financially literate counterparts. These households also demonstrate better debt management and budgeting control, leading to greater financial stability. In contrast, households with low financial literacy exhibit higher debt ratios, poor budgeting practices, and struggle with maintaining financial equilibrium. The findings highlight the importance of financial literacy in fostering responsible financial decision-making, reducing financial distress, and promoting long-term economic resilience. Furthermore, the study identifies gaps in existing research, particularly concerning low-income and marginalized groups in urban settings. Despite better access to financial services, urban areas still show significant disparities in financial literacy, particularly among specific populations such as Indigenous Australians. The study suggests that addressing these disparities through targeted financial literacy programs could enhance household economic outcomes and reduce inequalities. It also emphasizes the need for policy interventions to integrate financial education into urban communities, particularly for low-income or less-educated households. The study calls for future research to explore longitudinal impacts and extend the focus beyond urban areas to include rural populations, thus broadening the understanding of financial literacy’s role in economic stability across diverse contexts.